IMPROVING THE ABILITY OF THE SECOND GRADE STUDENTS OF SMPN 2 SINGARAJA IN MASTERING THE SIMPLE PAST TENSE THROUGH MODIFIED MEMORIZATION DRILL IN THE ACADEMIC YEAR OF 2014/2015 - ., Nyoman Purba Tribawa Giri; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Dr.Sudirman, M.L.S (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini betujuan untuk meningkatkan kemampuan siswa dalam menguasai simple past tense melalui modified memorization drill pada tahun ajaran 2014/2015. Jumlah subjek penelitian ini adalah 32 siswa, yang terdiri dari 18 perempuan dan 14 laki laki di SMP N 2 Singaraja. Tujuan penelitian ini adalah meningkatkan kemampuan siswa dalam menguasai simple past tense dan menjelaskan tentang bagaimana modified memorization drill meningkatkan kemampuan siswa di kelas VII.14. Penelitian ini berbentuk penelitian tindakan kelas. Data diperoleh dengan tehnik analisis quantitatif dan qualitatif. Data quantitatif dianalisa dengan menggunakan rumus penghitungan dan data qualitatif dianalisa dengan menggunakan kuisioner perilaku. Hasil dari penelitian membuktikan bahwa simple past tense bisa meningkat dengan menggunakan modified memorization drill. Ini bisa ditunjukan pada hasil quantitatif yang melebihi target minimum yaitu 84% (nilai tengah post test I 72.5 dan nilai tengah post test II 96). Nilai tersebut melebihi nilai ketuntasan minimal yang dibutuhkan oleh siswa kelas 2 di SMPN 2 Singaraja. Data qualitatif dari penelitian ini juga mendukung quantitatif data, yaitu siswa lebih rajin dan aktif, pada saat modified memorization drill digunakan dalam pelajaran bahasa inggrisKata Kunci : Modified memorization drill, Menguasai, Simple past tense This present study aimed at improving the students’ ability in mastering the simple past tense through modified memorization drill in the academic year of 2014/2015. The numbers of the subjects were 32 students, consisted of 18 females and 14 males in SMP N 2 Singraja. The purpose of the research are to improve the students ability in mastering simple past tense by using modified memorization drill and to discuss how modified memorization drill improve the ability of the second grade students in mastering simple past tense. This study was designed in the form of classroom action research. The obtained data were analyzed by quantitative and qualitative analysis techniques. Qualitative data used to analyze data from post test and quantitative data used to analyze data from questionnaires of attitude. The proved that the students’ ability in mastering simple past tense could be improved through modified memorization drill. The quantitative data analysis result in which students achieved the minimum target 84% (mean scored post test I was 72.5 and mean scored post test II was 96). This result exceeds the expected minimum score of success required by second grade of SMP N 2 Singaraja. The qualitative data of the study also support quantitative data, that is, the students are more diligent, and active, during the English teaching and learning process. keyword : Modified memorization drill, Mastering, Simple past tense